Trtangtu ning Bwana: Larangan Menangkap Ikan pada Prasasti Sang Hyang Tapak (952 Ś/ 1030 M) - I Gede Tangkas Yoga Brata; Coleta Palupi Titasari; Kadek Dedy Prawirajaya; Mira Agustini (Udayana University, 2025)
Research on the relationship between the prohibition on fishing in the Sang Hyang Tapak Inscription (952 Ś/ 1030 AD) with the religion of the Sunda Kingdom community is necessary to trace the reasons for determining fish as something important. This study raises two main problems: why did King Śrī Jayabhūpati order the prohibition of fishing and how its relationship to the sacred area mentioned in the inscription? This study was designed with the qualitative method, consisting of description, comparative analysis, critics and also interpretation. Based on the research that has been conducted, the prohibition on fishing in the Sang Hyang Tapak Inscription is related to the religio-political context of the reign of King Śrī Jayabhūpati who placed fish as the embodiment of God Vishnu. Through this fishing ban policy, Śrī Jayabhūpati tried to build good relations with religious groups while building a good image in accordance with religious texts.